2023
DOI: 10.1016/j.gpb.2023.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Duplication Reshaped Adaptive Evolution in a Relict Plant Species, Cyclocarya Paliurus

Abstract: Cyclocarya paliurus is a relict plant species that survived the last glacial period and shows a population expansion recently. Its leaves have been traditionally used to treat obesity and diabetes with the well-known active ingredient cyclocaric acid B. Here, we presented three C. paliurus genomes from two diploids with different flower morphs and one haplotype-resolved tetraploid assembly. Comparative genomic analysis revealed two rounds of recent whole-genome duplication events and identified 691 genes with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…The unique chromosome number was considered to be the distinctness of Cyclocarya from its sister genus Pterocarya [ 19 ]. However, Zheng et al [ 21 ] and Qu et al [ 22 ] recently found that C. paliurus includes autotetraploid individuals with 64 chromosomes. Therefore, the autotetraploid individuals may previously have been wrongly regarded as diploids with a unique aneuploid chromosome number.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique chromosome number was considered to be the distinctness of Cyclocarya from its sister genus Pterocarya [ 19 ]. However, Zheng et al [ 21 ] and Qu et al [ 22 ] recently found that C. paliurus includes autotetraploid individuals with 64 chromosomes. Therefore, the autotetraploid individuals may previously have been wrongly regarded as diploids with a unique aneuploid chromosome number.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the autotetraploid individuals may previously have been wrongly regarded as diploids with a unique aneuploid chromosome number. Considering that the sister genera Pterocarya and Juglans are diploid with 2 n = 2 x = 32, it is highly possible that C. paliurus is a naturally diploid–autotetraploid species [ 22 ], providing a powerful basis for investigating autotetraploid origins and genome evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclocarya paliurus is the only species in the family Juglandaceae and has medicinal, healthcare, material, and ornamental values. It is also called "Qing-qian-liu" or "Yaoqian-shu" because its fruit cluster is seen as a string of old Chinese copper coins [1][2][3]. Various bioactive constituents are found in the leaves of C. paliurus, including flavonoids, triterpenes, polysaccharides, and steroids, which have been shown to have pharmaceutical bioactivities [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…While exploring the improvement of rice yield, the nutritional quality and stress resistance of rice must also be increased. In nature, polyploids are extensively present ( Van de Peer et al., 2017 ; Qu et al., 2023 ). Most angiosperms, most eukaryotes, and crops such as rice have all undergone polyploidization during the course of evolution ( Xiong et al., 2022 ; He et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%